(untitled) (Research, Society and Development, 2024)
Idiopathic Thrombocytopenic Purpura (ITP) is a hematological disorder characterized by thrombocytopenia. The pathogenesis of this condition is mediated by autoantibodies directed at platelets and resulting in their elimination by the spleen. It can be asymptomatic and may present with mild, moderate or severe hematomas with a high risk of hemorrhage. Oral manifestations include bleeding, ecchymoses, petechiae, hemorrhages and mucocutaneous lesions. The aim of this study is to report a case of ITP with oral manifestations, provide a detailed description of the oral lesions, discuss diagnostic methods and therapeutic approaches. The presence of a dental surgeon in a hospital environment is of great importance for proper diagnosis and treatment, since oral manifestations are commonly observed as the first clinical signs of the disease. The dental surgeon can identify these symptoms early on and contribute to early diagnosis and the administration of appropriate care.